Absorção de água, germinação e dormência de sementes de mucuna preta - Galindo, Carlos Afonso Magalhães [UNESP] (2006)
Aiming to study damage and characterize possible relationships between size and physiological quality; size and coat permeability; physiological quality and tegument permeability; initial content of water and physiological quality of mucuna preta sedes (Stizolobium aterrimum Pierce & Tracy) the following experiments were conducted: análisis of water content of seed lots by oven meted at 105°C during 24 hours using with four replications of 100 seeds each; germination test (%G) and speed of germination index (SGI) with four replications of 25 seeds in complete randomized design; twelve treatments to break dormancy The seed lots presented inverse positive relationship for water content related to germination; treatment to break dormancy with interaction between lotsand seed sizes within lots; the tests demonstrated higher interaction between lots, occuring the inverse for the variable seed size; the imbibition curve proved to be na important tool in studies related with tegument permeabillity and levels of vigor among lots. The following conclusion can be withdrawn form data: small sedes are more permeable in nondormant lots; seed lots with similar germination or with lower water content, higher is the vigor; large sedes produce higher amount of phytomass. The best treatment to break seed dormancy of mucuna preta seed was acid escarification during seven minutes.